2019
DOI: 10.1111/aab.12480
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of marker‐assisted selection to improve maize for increased resistance to Sesamia nonagrioides attack with no detrimental effect on yield

Abstract: Two decades of investigations on maize resistance to stalk Mediterranean corn borer (Sesamia nonagrioides Lefebvre, MCB) corn borers have shown that breeding for increased resistance to stem tunneling by MCB often resulted in reduced yield because significant genetic correlation between both traits exists in some backgrounds. Unlike phenotypic selection, marker-assisted selection (MAS) could differentiate markers linked only to one trait from those linked simultaneously to increased resistance yield potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Indirect selection based on molecular markers (marker assisted selection; MAS) was initially based on quantitative trait loci (QTL) identified in a biparental population or as a subset of significant markers from genome wide association studies (GWAS). MAS has proven to be particularly effective for qualitative traits (Jiang, 2013;Das et al, 2017;Samayoa L et al, 2019), which are controlled by few genes with large effects, whereas, quantitative traits are controlled by many genes with small effects. For quantitative traits, indirect selection based on genomic prediction is considered a more appropriate and practical breeding tool over MAS (Jannink et al, 2010;Heslot et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Indirect selection based on molecular markers (marker assisted selection; MAS) was initially based on quantitative trait loci (QTL) identified in a biparental population or as a subset of significant markers from genome wide association studies (GWAS). MAS has proven to be particularly effective for qualitative traits (Jiang, 2013;Das et al, 2017;Samayoa L et al, 2019), which are controlled by few genes with large effects, whereas, quantitative traits are controlled by many genes with small effects. For quantitative traits, indirect selection based on genomic prediction is considered a more appropriate and practical breeding tool over MAS (Jannink et al, 2010;Heslot et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Two decades of research on maize resistance to MCB has demonstrated the high negative genetic correlation between yield potential and resistance. Such that pursuing higher resistance, measured as reduced tunnel length made by MCB in the pith, has significantly contributed to reduced kernel yield (Ordaś et al, 2010;Butroń et al, 2012;Jimeńez-Galindo et al, 2017;Samayoa et al, 2019). Although this negative relationship is not found in all genetic backgrounds (Samayoa et al, 2014;Jimeńez-Galindo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to PS could be Marker Assisted Selection (MAS) using markers linked to QTL with significant effects on resistance to stem tunneling by MCB but without adverse effects on yield (Ordaś et al, 2010;Samayoa et al, 2019). However, commonly employed MAS strategies are not suitable for improving complex agronomic traits, in part, due to the lack of power to capture small effect loci that are often important in the inheritance of these traits since many minor genes are involved in MCB resistance, measured as reduced pith gallery length, and yield (Butroń et al, 2009;Butroń et al, 2012).…”
mentioning
confidence: 99%
“…Therefore, MAS selection was envisioned as an alternative to phenotypic selection once genetic factors for resistance and yield could be disentangled. QTL studies for maize resistance to stem tunneling by S. nonagrioides larvae were carried out and MAS selection based on DNA markers flanking some QTLs was proven suitable to improve resistance without detrimental effects on yield (Ordas et al 2009(Ordas et al , 2010(Ordas et al , 2013Samayoa et al 2014Samayoa et al , 2015aSamayoa et al , 2015bSamayoa et al , 2019Jiménez-Galindo et al 2017. Nowadays, genomic selection is preferred over MAS selection approaches when traits are controlled by many genes with small additive effects as is the case for maize resistance and tolerance to stemborer attack.…”
Section: Varietal Resistance and Bt Technologymentioning
confidence: 99%